THE INFLUENCE OF INTERNAL AND EXTERNAL CORPORATE GOVERNANCE MECHANISMS TOWARDS AGENCY COST IN INDONESIA - Fanny Dinda Aditya; Tarmizi Achmad (Diponegoro Journal of Accounting, 2021)
This study aims to analyse the influence of internal and external corporate governance mechanisms towards agency cost in Indonesia by analysing the managerial ownership, board of commissioners, managerial compensation, auditor size, audit fees and agency cost.The population in this study consist of all banking industry in Indonesia for the period 2017 to 2019. Sample determined with purposive sampling method. The data is obtained from Indonesia Stock Exchange (IDX). The analysis technique used in this research is multiple linear regression using SPSS Statistics 26.The results of the analysis show that simultaneously, the five independent variables which include managerial ownership, board of commissioners, managerial compensation, auditor size, audit fees are significantly influence to agency cost. Partially, managerial compensation and auditor size have negative significant effect on agency cost, while managerial ownership, board of commissioners, and audit fees did not influence agency cost.